Amplifying the influence of Māori knowledge in environmental management. Issue 1 (March 2023) - Forster, Margaret
Modern mapping systems can provide almost everything there is to know about the environment, except what Māori know. So our interests are not that apparent in a mainstream context despite it being widely acknowledged that Māori have a unique and intergenerational relationship with the land- and waterscapes, and the presence of legislative requirements to reflect Māori political agenda in resource management decision-making. He Tātai Whenua is a project that seeks to assemble Māori knowledge and place it alongside existing environmental databases to render this knowledge highly visible and ensure a greater impact on Aotearoa New Zealand rights and environmental regimes. The challenge is constructing a process that maintains the integrity of Māori knowledge as it crosses into domains that are beyond the direct control of Māori communities as kaitiaki, guardians of that knowledge. In this article, He Tātai Whenua is the focal point of discussions around the importance of indigenous leadership, data sovereignty and a social justice agenda to maintain the integrity of Māori knowledge and navigate knowledge boundaries in the research activity. Two approaches are introduced. The first reflects on exchanges between knowledge systems to identify pathways that protect the integrity of Māori knowledge. The second considers how Māori environmental knowledge can be assembled and interact with science in a manner that makes sense from a Māori worldview. Together, these approaches enable us to develop a confidence in collaborative research and increased trust in how research outputs derived from Māori environmental knowledge will be used and applied to realise bicultural spatial governance.